Comparative evaluation of periodontal health status of pre and postmenopausal females - Neha Singh; Santosh Kumar Verma; Nitesh Kumar Sharma; Vivek Gupta; Awanindra Kumar Jha; Harsh Priyank (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Menopause in females is a corporeal stage that gives rise to a number of adaptive changes both at systemic and oral levels, prototypically occurring in the late fourth or fifth decade of life. Though physiological aging affects the oral tissue, the hormonal changes due to menopause also act as a major contributing factor in deteriorating the health of oral tissues. Thus, the main aim of our study was to compare the overall periodontal status and alkaline phosphatase levels in the saliva of females in their pre and postmenopausal ages. MATERIAL AND METHODS: This study was conducted on 200 female subjects coming to the Department of Periodontology at Rajendra Institute of Medical Science for oral prophylaxis. The subjects were arbitrarily selected in the age group ranging from 15 to 70 years and were further divided based on the inclusion criteria. Group A included 100 subjects with age ranging from 15 to 45 years, and group B, 100 subjects with age 54 to 70 years. Signs of periodontitis including clinical attachment loss, furcation involvement, and probing depth and salivary alkaline levels were obtained, evaluated, compared, and analyzed. RESULTS: In group A 65% of patients had grade 0 and 28% had grade 1 of clinical attachment level. Similarly in group B, 44% of the total had grade 0 of clinical attachment loss, 38% had grade 1, and 18% were of grade 2. On evaluating grades of furcation involvement, around 45% of the total patients in group A were grade 1 (incipient, pocket formation), while in group B, 51% of the total patients were grade 1. At least 46% in group A and only 20% in group B had no signs of furcation involvement. Salivary alkaline phosphatase levels in pre and postmenopausal patients showed a significant difference between the two groups was obtained. CONCLUSION: The study concluded a major difference in the periodontal health of pre and postmenopausal women with many influencing factors apart from menopause itself.